Examining the effect of consumer experience on co-creation and loyalty for healthy meat consumption - Meeprom, Supawat; Jaratmetakul, Porramate; Boonkum, Wuttigrai (Frontiers in Sustainable Food Systems, 2023)
Introduction The eating behavior of consumers throughout the world is changing rapidly due to increasing recognition of healthy food consumption. This study attempted to examine the role of perceived experience consumption responses in the context of healthy food consumption. In archiving the objectives of the study, this research investigates the relationship among the perception of customer sensory experience, customer co-creation, and customer loyalty (e.g., spreading positive word of mouth and recommending the food) of KKU1 premium chicken. This study also examines the moderating role of health consciousness in consumers' decision-making processes. Methods A purposive sampling survey of 487 customers who had consumed healthy chicken meat products, namely, KKU1 premium chicken in Thailand were collected. Multi-group analyses of the consumption experience (e.g., first-time and repurchase consumers) were examined. A structural equation model (SEM) was used to test the proposed hypotheses. Results The study found that customer co-creation has a significant positive effect on customer loyalty. In addition, the relationship between customer sensory experience and customer co-creation was moderated by health consciousness. This suggests that sensory experiences and health conscious customers are more prone to indulge in co-creation behavior. Moreover, there are different levels of customer co-creation behavior and loyalty among different prior consumption experiences. Discussion Based on these findings, including the contingency role of health consciousness in consumers' decision-making processes can be more effectiveness. These findings can provide an important reference for the producer of a healthy food-marketing strategy.